1979
DOI: 10.1111/j.1365-3091.1979.tb00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of berm development and resulting beach growth along a barrier spit complex

Abstract: Weekly topographic profile measurements across a southward migrating recurved‐spit complex throughout a summer period have revealed three different mechanisms of berm development, each reflected by a distinctive sedimentary sequence. Each mechanism dominates berm widening along certain sections of the active spit with transition zones separating each one. Along the straight beach sections where a net longshore transport is well developed, sand accumulates at the distal high‐tide swash mark during neap tide. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
115
1
8

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(133 citation statements)
references
References 12 publications
9
115
1
8
Order By: Relevance
“…Prograding coasts with a high sediment supply are the favourable sites for the preservation of ridge structures as noted by Van den Berg (1977), Hine (1979) and Beets et al (1981) among other authors. A sufficient supply of sediment and shelter from heavy storms appear to be of prime importan ce for a high preservation potential.…”
Section: )mentioning
confidence: 74%
See 3 more Smart Citations
“…Prograding coasts with a high sediment supply are the favourable sites for the preservation of ridge structures as noted by Van den Berg (1977), Hine (1979) and Beets et al (1981) among other authors. A sufficient supply of sediment and shelter from heavy storms appear to be of prime importan ce for a high preservation potential.…”
Section: )mentioning
confidence: 74%
“…As shown by Hine (1979), the internal structure of a berm is roade up of a cyclic pattern of horizontal parallellaminations arranged in fining-up sequences which represent the transition froro neap to spring tides. We found that this lateral succession of sequences tends to be overlain by seawardinclined para11el lamination also arranged in fining upward sequences (Fig. …”
Section: Mesotidal Coast (Gulf Of Cadiz)mentioning
confidence: 99%
See 2 more Smart Citations
“…The berm formation processes has been previously studied considering the effects of wave height, tidal fluctuations, water level changes induced by storms, sediment fall velocity, grain size or permeability (Bagnold 1940, Hine 1979, Weir et al 2006or Jensen et al 2009). But most of the studies dealing with berm formation, are qualitative studies, based on field experimental data highly affected by the tidal effect on gravel beaches.…”
Section: Introductionmentioning
confidence: 99%